A causal relationship between trade efficiency and economic efficiency: Evidence from dynamic simultaneous equations models. Issue 4 (19th May 2017) - Rasekhi, Saeed; Sheidaei, Zahra; Asadi, Seyed Peyman
ABSTRACT: The objective of this study is to examine the causal relationship between economic efficiency and trade efficiency using dynamic panel data in simultaneous equations models for global panel of 50 countries over the period 2000–2014. The study also implements this interrelationship for two groups of countries based on their level of development. Two models applying different factors reflecting countries' economic and trade policies are proposed to measure the targeted efficiencies using data envelopment analysis method. Evidence from the simultaneous equations models to identify a relationship between economic efficiency and trade efficiency supports the bidirectional causality between them in all three categories of countries. It has been also found that both economic and institutional factors have a significant positive influence on trade and growth performance, with the effect of political factors being especially pronounced for developing countries that suffer from weak institutional capacity. These empirical findings are of particular interest to policy-makers as they help to build sound policies in order to maximize trade performance as well as economic efficiency.